The mediating role of transmembrane protein 132D methylation in predicting the occurrence of panic disorder in physical abuse - Yu, Qianmei; Wang, Chiyue; Xu, Huazheng; Wu, Yun; Ding, Huachen; Liu, Na; Zhang, Ning; Wang, Chun (Frontiers in Psychiatry, 2022)
Objective: Genome Wide Association study (GWAS) has revealed that the transmembrane protein 132D (TMEM132D) is a gene of sensitive for panic disorder (PD). As the main type of childhood trauma experience, childhood abuse has become a public health issue attracting much attention at home and abroad, and has been proved to be a risk factor for the onset of PD. However, how it affects the occurrence and development of panic disorder has not yet been revealed. We examined the relationship between TMEM132D methylation, childhood abuse and symptoms based on this finding. Methods: Thirty-two patients with PD and 22 healthy controls (HCs) were recruited after age, gender, and the education level were matched. The DNA methylation levels of CpG sites across the genome were examined with genomic DNA samples (PD, N = 32, controls, N= 22) extracted from subjects' elbow venous blood. A mediation model was used to explore the relationship between the methylation degree of different CpG sites and childhood maltreatment and clinical symptoms. Results: We found that the PD group had significantly lower methylation at CpG1, CpG2, CpG3, CpG4, CpG5, CpG6, CpG7, CpG8, CpG11, CpG14 and CpG18 than did the HCs (p.05). The CpG2 (r= 0.5953, p=0.0117) site in the priming region of TEME132D gene were positively associated with PDSS score. The CpG2 (r= 0.4889, p=0.046) site in the priming region of TEME132D gene were positively associated with physical abuse. Furthermore, path analyses showed that the methylation of CpG2 of TMEM132D played a fully mediating role in the relationship between physical abuse and PD symptom severity (95％CI=0.0503 to 0.9136). Conclusion: Childhood abuse experiences, especially physical abuse, are significantly related to PD. The methylation of CpG2 of TMEM132D was shown to have a fully mediating effect between panic disorder and physical abuse. The interaction between TMEM132D methylation and physical abuse can predict panic disorder.